Problem Based Learning Model to Improve Analytical Thinking Skills of Grade XI Senior High School Students - Sri Rahmawati Dukalang; Astin Lukum; Julhim S Tangio; Mangara Sihaloho; Wiwin Rewini Kunusa (Universitas Negeri Gorontalo, 2026)
Thermochemistry remains one of the most challenging topics in senior high school chemistry because students are required to understand abstract concepts, perform quantitative reasoning, and connect chemical phenomena with real-life contexts. However, students’ analytical thinking skills in thermochemistry are often still limited, particularly in differentiating, organizing, and attributing information during problem-solving activities. This study aimed to examine the effect of the Problem Based Learning model on improving Grade XI students’ analytical thinking skills in thermochemistry. The research employed a quasi-experimental method with a non-equivalent control group pretest-posttest design. The study was conducted at SMA Negeri 1 Kabila during the first semester of the 2025/2026 academic year, involving 49 students divided into an experimental class taught using Problem Based Learning and a control class taught using conventional instruction. Data were collected using a nine-item essay test and analyzed through normality, homogeneity, independent-samples t-test, and N-Gain analysis. The results showed that the data were normally distributed and homogeneous. The independent-samples t-test indicated a significant difference between the two classes, with tcount = 4.055 exceeding ttable = 1.678. The N-Gain results also showed that the experimental class achieved higher improvement across all analytical thinking indicators than the control class. These findings imply that Problem Based Learning is an effective instructional model for strengthening students’ analytical thinking skills in thermochemistry.